Pengaruh Inflasi Dan Tingkat Suku Bunga Terhadap Harga Saham Pada Bank Bumn Yang Teraftar Di Bursa Efek Indonesia Periode 2015-2019 - Agus Agus; Aryati Arfah; Baharuddin Semmaila (STIE AMKOP, 2021)
This study aims to examine as well as examine this study aims to determine the effect of the variable inflation and interest rates on stock prices. The research hypothesis uses a theory/concept basis, supported by previous studies that have the same variables. The type of data used is secondary data. The number of samples in this study were 4 commercial banks owned by State-Owned Enterprises (BUMN). This study uses primary data collected using a questionnaire. Furthermore, the data were analyzed using the SPSS statistical tool using the multiple regression analysis method. The data were tested through several stages of testing such as normality, heteroscedasticity and multicollinearity tests. Furthermore, to prove the hypothesis proposed in this study, it will be seen through the coefficient of determination test, partial test (t-test). The results of this study indicate that inflation has a positive and insignificant effect on stock prices of state-owned banks listed on the Indonesia Stock Exchange. This shows that inflation cannot be used as a benchmark for investors to invest in the stock market. Interest rates have a negative and insignificant effect on stock prices of state-owned banks listed on the Indonesia Stock Exchange. This shows that the interest rate cannot be used as a benchmark for investors to invest in the stock market. Keywords: Inflation, Interest Rate, Stock Price